New species and records of Arrenurus from the Paraná river, Argentina (Acari: Parasitengona: Arrenuridae) - Beatriz, Rosso De Ferradás (Zootaxa, 2006)
Arrenuridae inhabiting the Paraná river basin show great diversity relative to that of this family in Argentina and other Neotropical regions, with 38 species (35 studied by the author). In this new contribution Arrenurus mocovi n.sp. is described and A. (Arrenurus) trichophorus Daday is recorded for the first time. The female of this latter species is redescribed and data for the males are added, as well as the geographic distribution of the species. For Arrenurus imperator imperator Lundblad, a Brazilian species, morphometric characteristics are given. The recently created subgenus A. (Brevicaudaturus) is analyzed, within which the last species plus three other neotropical taxa are placed.